Influence of sintering temperature on mechanical properties of biologically derived hydroxyapatite bodies - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
The properties of sintered hydroxyapatite (HA), obtained from bovine femoral shafts via calcination method, were investigated utilizing scanning electron microscopy (SEM) and X-ray diffraction analysis together with measurements of microhardness, density, and compression strength. The production of HA from natural sources is preferred due to money and time saving reasons. The results indicate the new HA materials as promising in biomedicine, since similar mechanical behaviour was obtained with previous studies.
Keywords: Hydroxyapatite; Mechanical Properties; Sintering